2020
DOI: 10.3390/ijerph17103644
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Subtractive Proteomics Approach for Identification of Potential Drug Targets in Staphylococcus saprophyticus

Abstract: Staphylococcus saprophyticus is a uropathogenic bacteria responsible for acute urinary tract infections (UTIs) mainly in young female patients. Patients suffering from urinary catheterization, pregnant patients, the elderly as well as those with nosocomial UTIs are at greater risk of the colonizing S. saprophyticus infection. The causative factors include benign prostatic hyperplasia, indwelling catheter, neurogenic bladder, pregnancy, and history of frequent UTIs. Recent findings have exhibited that S. saprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Three proteins from this study predicted to be involved in the biosynthesis of secondary metabolites are unique to M. genitalium . This is similar to reports from other studies where the proteins associated with this pathway have been described to be essential, non-homologous, and unique to different bacteria pathogens such as Vibrio parahaemolyticus and Staphylococcus saprophyticus [ 23 , 37 ]. Different studies have reported the manipulation of bacterial secondary metabolites pathways and their use as antibiotics, antiviral drugs, and other pharmaceutical drugs [ 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 91%
“…Three proteins from this study predicted to be involved in the biosynthesis of secondary metabolites are unique to M. genitalium . This is similar to reports from other studies where the proteins associated with this pathway have been described to be essential, non-homologous, and unique to different bacteria pathogens such as Vibrio parahaemolyticus and Staphylococcus saprophyticus [ 23 , 37 ]. Different studies have reported the manipulation of bacterial secondary metabolites pathways and their use as antibiotics, antiviral drugs, and other pharmaceutical drugs [ 38 , 39 , 40 , 41 ].…”
Section: Resultssupporting
confidence: 91%
“…A total of 10 S. pyogenes essential proteins were involved in these 6 pathways. The results of pathogen-specific pathway identification are consistent with those reported by Goyal et al, Amineni et al, and Shahid et al for A. baumannii, L. interrogans, and S. saprophyticus, respectively [13,55]. Eight out of the ten proteins were found to be involved in H. sapiens and S. pyogenes pathways.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison with traditional methods, these methods save time, are faster, and are more cost-effective in the drug design process [11]. Using the subtractive proteomics approach, potential targets and vaccine candidates for various pathogenic bacteria have been identified over the last several years [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In silico subtractive approaches, besides being time saving, are cost effective in drug research and development stages [ 15 ]. These approaches were used to identify potential drug targets in many pathogens, including Acinetobacter baumannii , Burkholderia pseudomallei , Mycobacterium avium , Neisseria meningitides , Pseudomonas aeruginosa , Staphylococcus saprophyticus , and Streptococcus pneumoniae [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Similarly, several potential drug targets in H. pylori were also identified [ 12 , 23 , 24 , 25 , 26 ]; however, none of these studies predicted possible drug binding ligands, except for a study that proceeded to druggability analysis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%